The impact of early molecular response in children and adolescents with chronic myeloid leukemia treated with imatinib: a single-center study from China. Issue 9 (2nd September 2018) - Shao, Haigang; Zeng, Zhao; Cen, Jiannong; Zhang, Jun; Bai, Shuxiao; Wu, Chunxiao; Gong, Yanlei; Wang, Yong; Qiu, Huiying; Chen, Suning; Pan, Jinlan
Abstract: Chronic myeloid leukemia (CML) is rare among children and adolescents. The early molecular response (EMR) is an important prognostic significance for adult CML patients. This study explored the impact of EMR on the prognosis in 40 children and adolescents with CML-CP treated with imatinib (IM). Our results showed that a high proportion of patients failed to achieve the BCR-ABL1/ABL1 International Scale (IS) ≤ 10% at 3 months. Children with a BCR-ABL1/ABL1 ≤ 10% at 3 months and <1% at 6 months increased the rate of achieving complete cytogenetic response (CCyR) and/or major molecular response (MMR) at 12 months compared to those with BCR-ABL1/ABL1 > 10%. With a median follow-up of 42 months, patients with BCR-ABL1/ABL1 ≤ 10% showed a better 4-year event-free survival (EFS). In summary, achieving BCR-ABL1/ABL1 IS ≤10% at 3 months and <1% at 6 months would increase the possibility of achieving MMR, CCyR at 12 months and had a better 4-year EFS. EMR is a reliable prognosticator for young CML patients treated with IM.